Challenges of Integrating Translation into Communicative Language Teaching: Lived Experiences of English Teachers in an Indonesian Islamic Primary School - Rahmat Syukran; Veni Roza; Widya Syafitri (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The integration of Translation into Communicative Language Teaching (CLT) has regained attention in multilingual and religiously oriented educational contexts. In Indonesian Islamic primary schools (Madrasah Ibtidaiyah), English teachers regularly move between English, Indonesian, Arabic, and local languages, creating tension between communicative ideals and classroom realities. Yet little is known about how teachers themselves experience this tension. This study explores the lived experiences of English teachers at Madrasah Ibtidaiyah Raudhatul As-Salimy, Koto Tangah, Tilatang Kamang, Agam Regency, in integrating translation into CLT. Using a Qualitative Phenomenological Design, data were generated through Semi-Structured Interviews, Classroom Observations, And Document Analysis involving five purposively selected teachers. The findings reveal four interconnected challenges: Ideological Tension Between CLT Principles And Translational Necessity, limited competence in using translation strategically as pedagogical scaffolding, institutional pressure from an Islamic curriculum that prioritises Arabic and religious subjects; and minimal student exposure to English beyond the classroom. The study shows that translation is not experienced merely as a teaching shortcut, but as a context-driven response to Communicative Breakdown, Curricular Pressure, And Learner Need. It concludes that translation can function as a legitimate scaffold within CLT when used reflectively. These findings have implications for teacher education and curriculum design in Islamic primary education.